Improved ${\bi l}_{\bf 0}$l0-RLS adaptive filter - Das, B.K; Chakraborty, M (Electronics letters, 2017)
In this Letter, the authors present an improved sparse recursive least squares (RLS) algorithm, which employs a novel approximation of the $l_0$l0 norm of the filter coefficient vector for regularising the RLS cost function. The proposed algorithm achieves improved performance over existing algorithms as demonstrated via numerical simulations.